IMPLEMENTATION OF SAK EMKM ON MICRO SMALL MEDIUM ENTREPRISES (CASE STUDY: BU EKO'S SOSIS SHOP) - Abednego Priyatama; Jessica Barus; Ratna Susilowati (Asosiasi Dosen Muda Indonesia, 2023)
SAK-EMKM is the financial accounting standard that regulates general transactions and the measurement basis uses historical costs, so that EMKM simply records assets and liabilities at their acquisition cost. It is hoped that SAK-EMKM can assist MSME actors in Indonesia in preparing financial reports to make it easier for MSME actors to obtain access to funding from financial institutions. The purpose of this research is to identify whether Bu Eko's Sausage Shop has implemented SAK EMKM. The results of observations and analysis can be concluded that in this business adequate financial reporting has not been implemented. Kedai Sosis Bu Eko has not been able to measure the level of financial performance and has not been able to know clearly and with certainty the development of its business.